Ekologi Tanaman Jeruju Hitam (Acanthus ilicifolius) dan Jeruju Putih (Acanthus ebracteatus) di Bali - Abimanyu, Ahnaf; Wirawan, I Gede Putu; Suada, I Ketut (Nandur; Vol 2 No 3 (2022), 2022)
Jeruju is a genus of Acanthus which is divided into two types, namely white jeruju and black jeruju. These two types of plants are found naturally growing wild in areas with wetlands around downstream and river mouths, along the coast, and swamps, especially in Bali as mangrove vegetation. Both jeruju plants have the ability as environmental phytotechnology. Therefore, it is necessary to study the environmental habitat of the black and white jeruju plants. This study aims to determine the habitat of black and white jeruju plants which can be used as a basis data for conservation efforts. The research method was carried out by observing the biotic and abiotic environment in the black and white jeruju habitats. The results showed that black jeruju plants grow in swamp habitats, clay soil structures with a pH value of 6 and some mangrove plants as the surrounding vegetation. However, the white jeruju grows in coastal habitats, sandy loam soil structures with a pH value of 5 and no vegetation around it.